(untitled) (Research, Society and Development, 2021)
In recent years, the increase in the search for medicinal and nutritional alternatives in the field of health has led to the search for plants present in the daily lives of the population. Consequently, several surveys aimed to assess the potential and health benefits. Therefore, the objective of the study is to carry out a literature review on the potential medicinal and nutritional use of the Ilex paraguariensis plant. Researches were carried out in the databases PubMed, EMBASE, Virtual Health Library (VHL), Cochrane Library, Web of Science, using the descriptors selected in MeSH, DeCs and Entree. The searches were carried out in the period of January 2020. The inclusion criterion used included articles from the last 20 years, including literature reviews. After the searches, 12 articles were selected to compose the literature review. Ilex paraguariensis showed capacity for antimicrobial and anti-inflammatory activity. The extracts of yerba mate were able to inhibit microorganisms: Salmonella enteritidis, Candida albicans, Proteus mirabilis, Pseudomas aeruginosa, Staphylococcus aureus, Staphylococcus epidermidis, Staphylococcus mutans, Listeria monocytogenes, Propionibacterium acnes, Enterobacteri cloacae, Bacillus cereus, Micrococcus flavus, Aspergillus fumigatus, Aspergillus versicolor, Aspergillus ochraceus, Aspergillus niger, Candida crusei, Penicillium funiculosum, Penicillium verrucosum var. ciclopium, Klebsiella pneumoniae, Enterobacter agglomerans, Enterobacter aerogeneses, Serratia marcesens, Proteus mirabilis. However, there was no consensus in the literature on activity against Escherichia coli, Enterococcus faecalis and Acinetobacter baumannii. Thus, yerba mate has an antimicrobial potential under some microorganisms, but further studies are needed for a more efficient analysis of the action against bacteria and a possible clinical application.